The Influence of Intellectual Capital Disclosure and Profitability on Company Value - Rizky Adzan Maulana; Elis Mediawati (Universitas Pendidikan Indonesia, 2022)
This study aims to determine the effect of intellectual capital disclosure and profitability on company value. The sampling method used is purposive sampling with a sample of 67 companies in the manufacturing sector in the period 2018 to 2020. The hypothesis test uses multiple linear regression analysis and the F test which is processed using SPSS software. The test results show that each variable of intellectual capital disclosure and profitability has a positive effect on company value. And simultaneously variable intellectual capital disclosure and company value have a positive effect on company value. The results of hypothesis testing show that intellectual capital disclosure and profitability are information that is considered a positive signal by investors so that it helps increase the value of the company. The implications of this research are aimed at companies and future researchers. The implication of this study concludes that the disclosure of intellectual capital disclosure and company profitability is positive information that will meet the information needs of investors so as to increase company value. This study uses different proxies in measuring research variables and there are also differences between companies and years of research.